Evaluating for learning and accountability in system innovation: Incorporating reflexivity in a logical framework. (June 2017) - Botha, Neels; Coutts, Jeff; Turner, James A; White, Toni; Williams, Tracy
Approaches to accelerate innovation have become more integrated and systemic over time, such as Agricultural Innovation Systems and co-innovation. Primary Innovation is a New Zealand co-innovation programme in which innovation is conceived as being 'co-produced' by stakeholders who contribute their unique knowledge to solving a problem or realizing an opportunity. In co-innovation, cyclical processes of planning, doing, observing and reflecting enable innovation to emerge from interactive learning among stakeholders. In this article, we argue that when flexibly applied and adapted to capture dynamics typical in systems innovation projects, the log frame approach and logical frameworks have considerable utility to support evaluation for both learning and accountability and for identifying and addressing institutional logics, which lead to system innovation. We demonstrate this for the case of Primary Innovation and compare our experiences with the limitations and solutions suggested by other recent researchers when applying logic models, logical frameworks, programme theories or theories of change as part of an 'adapted accountability framework'.